2001
DOI: 10.1590/s0101-81752001000500027
|View full text |Cite
|
Sign up to set email alerts
|

Territorial-like defensive behavior of floral resources by Heliconius ethilla narcaea Godart over H. sara apseudes (Hübner) (Lepidoptera, Nymphalidae, Heliconiinae)

Abstract: The use of nectar and pollen of a bromeliad by two heliconiine butterflies, Heliconius ethilla narcaea Godart, 1819 and H. sara apseudes (Hübner, [1813]) (Lepidoptera, Nymphalidae, Heliconiinae), is herein reported. Observations were made during a pollination study of Aechmea gracilis Lindman (Bromeliaceae, Bromelioidea) in a second-growth forest of the village Vila Dois Rios, Ilha Grande, Rio de Janeiro State, southeastern Brazil. Field observations showed that H. ethilla can be more aggressive than H. sara i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Learning to prefer different flower colours could be beneficial if two butterfly species are competing for resources. For example, the difference in spontaneous flower preferences shown by the two Lycaena species could be due not to dissimilar perceptual capabilities but to ecological factors such as aggressive competition for floral resources, as was observed in two Brazilian Heliconius species (Rocha & Duarte, 2001). Although the flower units of A. alpicola and E. speciosus did not differ in either nectar volume or concentration, it is also possible that the two Lycaena species could respond differently to other floral characteristics such as amino acid composition of the nectar and/or flower scent.…”
Section: Preferencesmentioning
confidence: 96%
See 1 more Smart Citation
“…Learning to prefer different flower colours could be beneficial if two butterfly species are competing for resources. For example, the difference in spontaneous flower preferences shown by the two Lycaena species could be due not to dissimilar perceptual capabilities but to ecological factors such as aggressive competition for floral resources, as was observed in two Brazilian Heliconius species (Rocha & Duarte, 2001). Although the flower units of A. alpicola and E. speciosus did not differ in either nectar volume or concentration, it is also possible that the two Lycaena species could respond differently to other floral characteristics such as amino acid composition of the nectar and/or flower scent.…”
Section: Preferencesmentioning
confidence: 96%
“…In this light, it is interesting that L. heteronea and L. rubidus preferred different flower species (and presumably colours). For example, the difference in spontaneous flower preferences shown by the two Lycaena species could be due not to dissimilar perceptual capabilities but to ecological factors such as aggressive competition for floral resources, as was observed in two Brazilian Heliconius species (Rocha & Duarte, 2001). First, two butterfly species may prefer different flower colours due to innate or learned preferences.…”
Section: Preferencesmentioning
confidence: 96%
“…Seventy-four forest sites in the Bolivian Andes and adjacent lowlands contained 188 bromeliad species whose pollination modes were judged as 115 by birds, 45 by insects, 14 by bats, eight self-pollinated, and six mixed; terrestrial forest bromeliads showed mainly insect pollination as did bromeliads at arid sites (Kessler and Kromer, 2008). In eastern Brazil, the butterfly Heliconius ethilia narcaea Godart was more aggressive than H. sara apseudes (Hübner) (Lepidoptera: Heliconiidae) when both were exploiting nectar and pollen of Aechmea gracilis Lindman (Rocha and Duarte, 2001). In eastern Brazil, visits to Aechmea , Billbergia , Nidularium , Tillandsia , and Vriesia bromeliads, were recorded as 62.5% by butterflies to Tillandsia spp., and 72–96% by hummingbirds to species of the other four genera (Varassin and Sazima, 2000).…”
Section: Arthropods As Pollinators Of Bromeliadsmentioning
confidence: 99%